Trend, Eksistensi, Peran Dan Fungsi Media Televisi Swasta Nasional Dalam Konteks Kesejahteraan Secara Ekonomi Dan Kemandirian - Hanafi . (Universitas Informatika dan Bisnis Indonesia, 2020)
This paper uses the framing analysis method, especially from the content approach, ideology and media economy which not only analyzes literary discourse but also describes the analytical and interpretative aspects of writing related to the existence and business of national private media in Indonesia. The results of the study provide an explanation of the meaning of media existence, media freedom raises the problem of the concentration of ownership of media companies (conglomerates), which changes the face of media freedom and the need for public information to become the freedom to control the media market. In terms of ideological attachment, the progress of television media cannot be separated from the ideological thoughts and interests of its media crews. Economically, the press is recognized as an economic institution, although its purpose is limited to the welfare of employees (Article 3 Paragraph 2 of the 1999 Press Law). The content of the Television Broadcasting Program, shows more packages and contents that are set according to the political and economic interests of the media owners and according to the ideological framework of the media crews. Meanwhile, from the organizational side, the media is more tied to the structure and hierarchy of power (which is built for the interests of the authority of the media owners) itself. Furthermore, from the culturalist side, the media has entered into the global industrial era, and there are structural boundaries that make not all the idealistic values ​​of the press can be realized